The New Products of Consumption-Oriented Architecture in Recent Years: Residences - Yuksel, Uygar; Akbulut, M. Tolga (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2009)
In recent years, particularly in Istanbul and other major cities, the important building type that offers a new lifestyle, as objects of consumption, is residences. The concept of residence that has been widely used in the construction sector accommodates a variety of different meanings according to the defined building's intended use, construction year, construction place, and target users. Even if the concept is often used across the different disciplines, its definition is still not fully defined and goes beyond the lexical meaning. Therefore, it was intended in this study to define residence over different partners in the construction sector, as architects, investors, real estate marketing experts, and users. It was also aimed to identify reasons for the formation and preferences of residences and to discuss the results in the context of Istanbul.
Keywords: Istanbul; luxury houses; residence; consumption-oriented architecture; Architecture